Evaluation of the macula, retinal nerve fiber layer and choroid thickness in postmenopausal women and reproductive-age women using spectral-domain optical coherence tomography - Ataş, Mustafa; Açmaz, Gökhan; Aksoy, Hüseyin; Demircan, Süleyman; Göktaş, Altan; Arifoğlu, Hasan Basri; Zararsız, Gökmen (Menopause Review/Przegląd Menopauzalny, 2014)
Objective: Menopause is a physiological life period that potentially affects various organs and systems. Therefore, a wide spectrum of signs and symptoms of eyes may be clinically observed in the postmenopausal period. Aim of the study : To evaluate the macular, retinal nerve fiber layer (RNFL) and choroidal thickness alterations by using spectral-domain optical coherence tomography (SD-OCT) in postmenopausal women and compare with healthy reproductive-age women controls. Material and methods: The study population included a healthy reproductive-age control group (n = 72) and postmenopausal study group (n = 72). Retinal thickness parameters were measured by SD-OCT. Peripapillary RNFL thickness parameters, macular thickness and choroidal thickness were evaluated. Results : Superior inner macula, temporal inner macula, inferior inner macula, nasal inner macula, inferior outer macula and choroid thickness were significantly thinner in the postmenopausal study group than the healthy reproductive-age control group (p = 0.007, p = 0.037, p = 0.027, p = 0.006, p = 0.016, p < 0.001, respectively). After adjusting for age, only choroid thickness was significantly thinner in the postmenopausal study group than controls (p† = 0.005). Conclusions : This study revealed that choroidal thickness measured by SD-OCT was significantly thinner in postmenopausal women than healthy reproductive-age women. We can speculate that the decrease in choroidal thickness in postmenopausal women may indicate a reduced estrogen-dependent vasodilatory effect in ophthalmic artery secondary to menopausal estrogen deficiency.